2015
DOI: 10.1007/s10439-015-1482-5
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Phase Contrast Allows Three Dimensional, Quantitative Imaging of Hydrogel Implants

Abstract: Three dimensional imaging techniques are needed for the evaluation and assessment of biomaterials used for tissue engineering and drug delivery applications. Hydrogels are a particularly popular class of materials for medical applications but are difficult to image in tissue using most available imaging modalities. Imaging techniques based on X-ray Phase Contrast (XPC) have shown promise for tissue engineering applications due to their ability to provide image contrast based on multiple X-ray properties. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…XPC imaging is a developing category of X-ray techniques that have shown significant potential for imaging biomaterial and soft tissue structures that are difficult to observe with other imaging modalities. Specifically, these techniques have been successful in observing hydrogels in tissue 30,31,35 and low-density scaffolds in water 46 and soft tissue. 33,34 The techniques enable highresolution, large volume imaging of these materials, without the need for exogenous contrast agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…XPC imaging is a developing category of X-ray techniques that have shown significant potential for imaging biomaterial and soft tissue structures that are difficult to observe with other imaging modalities. Specifically, these techniques have been successful in observing hydrogels in tissue 30,31,35 and low-density scaffolds in water 46 and soft tissue. 33,34 The techniques enable highresolution, large volume imaging of these materials, without the need for exogenous contrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal imaging technique would not require exogenous contrast and be nondestructive. X-ray phasecontrast (XPC) imaging is a class of X-ray-based techniques that enable imaging of biomaterial and soft tissue structures, [30][31][32][33][34][35] which are difficult to observe using other imaging modalities. These techniques enable high-resolution and large volume imaging of these samples in the absence of exogenous contrast agents.…”
mentioning
confidence: 99%
“…Consequently, CT has been extensively used in different bone TE applications [66,67,68,69]. The development of more sensitive techniques like micro-CT has allowed for the study of the morphology and 3D structure of different scaffold geometries in the sub-micron scale as well as the tracking of different cells incorporated into the scaffold structures [70,71,72,73,74,75,76]. These unique advantages have also allowed CT to be used in conjunction with new additive manufacturing techniques, such as 3D (bio)printing, for different implant-manufacturing purposes [66].…”
Section: Scaffold Tracking Techniquesmentioning
confidence: 99%
“…During the first week after implantation, animals had daily micro CT scans, which clearly showed the presence of biomaterial in the abdomen. Likewise, Appel et al [110] showed that XPC CT application allows 3D visualization and quantification of hydrated soft tissues and PEG hydrogels in vivo, with no contrast agents. The XPC CT imaging enabled a clear distinction between surrounding tissue after transplantation and the hydrogel structure.…”
Section: X-raymentioning
confidence: 99%